Relationship between biogas production and variations in electric resistivity in landfill of rio Claro city, Brazil - Moreira, César Augusto [UNESP]; de Castro, Marcus Cesar Avezum Alves [UNESP]; Carrazza, Leonardo Paioli [UNESP]; Cavallari, Fernanda [UNESP]; Helene, Lívia Portes Innocente [UNESP]; Machado, Fabio Braz (My University, 2015)
This work relates measures of the biogas flow in drains located on landfill with measurements of electric resistivity, obtained by the technique of geophysical logging by measuring cable installed in two vertical boreholes near to two biogas drains, with different flows. The results indicate that variation in rainfall, generation and accumulation of biogas in landfill, are repairable correlation with oscillations in electrical resistivity measures. The biogas production is apparently conditioned by age of residues and organic matter available from the degradation. The biogas drain in region with low production of biogas does not present resistivity pattern directly or indirectly correlated to biogas production, while the biogas drain in region with high gas production was characterized by high resistivity values, with seasonal variation by influence of rainfall.
Keywords: DC resistivity; Logging; Methane; Organic matter; Rainfall